An investigation into the factors influencing consumers to use e-services of Indonesian airlines: The role of motivation - Urumsah, Dekar; Quaddus, Mohammed; Galbreath, Jeremy (Aalto University, Finland, 2011)
E-Services have been a popular area of research. This research explores what pushes consumers to use Indonesian airline e-Services. Specifically, this study investigates into how the ‘motivation’ factor can be combined in some traditional theoretical models, within which it studies the influence on intention of the customers to use e-Services as well as its usage. A positivist paradigm is referred to conduct the research using a two-stage sequential mixed method research approach comprising both field study and quantitative methods. The field study has been employed to refine the research model and quantitative data collected from questionnaire-based survey is analyzed by using Partial Least Square (PLS) based Structural Equation Model (SEM). The research model is validated by surveying 819 Indonesian consumers who have used Indonesian Airline e-Services. The results confirm behavioral intention to use is influenced by the effort expectancy, social influence, outcome expectancy, and motivation. The motivation itself is influenced by the effort expectancy, social influence, trustworthiness, and outcome expectancy. Findings indicate that the effort and outcome expectancy are both influenced by trustworthiness and facilitation conditions. The results also demonstrate that motivation drives e-Services usage directly or indirectly through the intention to use. Furthermore, the implications of the findings are highlighted.